Perilaku Karyawan sebagai Study Etnografi - Rizal Rahmawan; Andi M Rudhan (Neolectura, 2021)
The behavior of employees in an organization increases organizational effectiveness, to be able to achieve employee behavior that provides organizational benefits, organizations must internalize work culture to individuals. This study aims to reveal the application of ethnography in organizations through employee behavior. The method used is qualitative with a literature study. Research result. Showing the organization in developing and maintaining the integrity of the organization from the point of view of the behavior of its employees is to ensure that the individual needs and desires which are the main motives of the individual behave are equated, relevant, equated, with the vision and mission of the organization, that way, the process of internalizing the individual to the organizational culture can be effective. takes place without going through a variety of time-consuming and material treatments.